A Magyar Pedagógia folyóirat tudománymetriai elemzése a hivatkozási szokások és a hivatkozási hálózatok tükrében - Nagy, Gyula; Molnár, Gyöngyvér (Magyar Pedagógia, 2018)
The aim of this paper is to discuss the results of the citation analysis of the journal Magyar Pedagógia. The current study is the second part of our complex research project, which consists of three main pillars: metadata, citation and content analysis. This paper focuses on the second issue, i.e. analyzing the features of citations, such as variety, age, quantity and their other characteristics. In addition to these results, the study reveals the visual structure of the citation network of the journal. The cited authors and their affiliation were identified on a citation graph. The journal introduced a unified and consequent reference style in 1991 based on the APA citation format; therefore, our sample comprises those scientific articles (N=429) which had a standard reference list. The examined period included all publications meeting these conditions between 1991 and 2014. After the citations (N=14,039) had been automatically detected and extracted, a structured database was set up enabling a specific investigation. Besides, a general statistical analysis of citations, the most significant authors’ impacts, their institutional backgrounds and the number of citations by authors are also discussed. The following indicators were assessed: the most-cited authors, genre, interdisciplinarity, international and national references, and the freshness of citations. To visualize the scientific connections, two citation graphs were created: one for the journal citation space and another with all the citations that had a full citation network. The latter graph is enormous as it consists of five components and has 10,382 nodes with 19,182 edges between them.